Framework for a multi-criteria decision support system for water permit allocation in Brazil - Carlos Ueslei Rodrigues de Oliveira; Peter Zeilhofer (Revista Brasileira de Recursos Hídricos)
ABSTRACT This study presents an operational framework for a decision support system (DSS) aligned with Brazilian water resource legislation, designed to manage the allocation of surface water resources (WRA) through water permit concessions, aimed at resolving conflicts between competing users seeking withdrawals and effluent dilution. The DSS integrates a one-dimensional model for assessing water availability with a multi-criteria decision analysis module, employing the Analytic Hierarchy Process combined with fuzzy logic for criteria weighting. When simulated water availability falls below sustainable limits for a new water use permit, the system triggers a processing scheme to propose reallocation scenarios for withdrawals and effluents among new and existing upstream users. The DSS then provides ensembles of optimal solutions to ensure that previously defined minimum water availability targets are met in the stream. A case study in the Cuiabá River basin validates the functionality of the modular system. Given the decentralized and participatory nature of Brazilian water resource legislation, the WRA-DSS framework is flexible and prepared for the inclusion of new decision criteria or water protection goals, as well as the integration of more advanced flow and water quality models.